2019
DOI: 10.3389/fped.2019.00331
|View full text |Cite
|
Sign up to set email alerts
|

AST-to-Platelet Ratio Index as Potential Early-Warning Biomarker for Sepsis-Associated Liver Injury in Children: A Database Study

Abstract: Background: Sepsis-associated liver injury (SALI) is a risk factor of poor outcome in patients with sepsis. The early warning biomarkers for identifying SALI remain poorly defined. Aims: To identify the potential predictors of occurrence of SALI in pediatric patients with sepsis. Methods: We retrospectively analyzed the sepsis database based on the medical records of patients admitted to the pediatric intensive care unit (PICU) in Shanghai Children's H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Early onset neonatal sepsis can be predicted by platelet/lymphocyte ratio (Arcagok and Karabulut, 2019). A high level of platelet-derived growth factor B (PDGFB) is found in survivors of sepsis (Dou et al, 2019), and PDGFB can reduce the mortality of sepsis by blocking inflammatory responses (Dou et al, 2019). In sepsis-associated liver injury, AST/platelet ratio might be an early onset predictor (Dou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early onset neonatal sepsis can be predicted by platelet/lymphocyte ratio (Arcagok and Karabulut, 2019). A high level of platelet-derived growth factor B (PDGFB) is found in survivors of sepsis (Dou et al, 2019), and PDGFB can reduce the mortality of sepsis by blocking inflammatory responses (Dou et al, 2019). In sepsis-associated liver injury, AST/platelet ratio might be an early onset predictor (Dou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A high level of platelet-derived growth factor B (PDGFB) is found in survivors of sepsis (Dou et al, 2019), and PDGFB can reduce the mortality of sepsis by blocking inflammatory responses (Dou et al, 2019). In sepsis-associated liver injury, AST/platelet ratio might be an early onset predictor (Dou et al, 2019). The underlying mechanism of platelet dysfunction in sepsis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Kobashi, H et al [3] demonstrated that the poor prognosis ratio(the proportion of the patients who died or whose condition had worsened or was unchanged)of SALI was 50.6% in a retrospective cohort study. Dou, J et al [11] demonstrated that hospital mortality of pediatric patients with SALI was 23.81%. Y. R. KANG et al [9] demonstrated that ICU mortality in septic shock patients with hepatic dysfunction was 36% and in-hospital mortality was 48% in a retrospective observational study.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, severe bacterial infection can cause septicemia, and sepsis has been recognized as a global health priority by WHO because of the current estimates of 30 million episodes and six million deaths per year [ 1 ]. And the life-threatening organ dysfunction caused by dysregulated host response to infection is a thorny issue in sepsis [ 2 ], including liver injury, one of the main clinical manifestations and an independent risk factor for multiple organ dysfunction syndrome (MODS) and high mortality rate in patients with sepsis [ 3 ]. Hepatic dysfunction is considered to be one component of the MODS and usually associated with a poor prognosis in clinic during sepsis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%